Pengaruh Pergerakan Harga Saham Sektor Perbankan dan Nilai Tukar Rupiah/Dollar Terhadap IHSG di Bursa Efek Indonesia Periode 2006 - 2009 - , Ferry Indra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As we know that the crisis happens in 1998 have plagued the world, including Indonesia. However, in the case of Indonesia, for example, the results of the stress test shows that the national banking conditions in general are relatively stable. Various indicators in support of these conditions, such as banking capital nationally and capital adequacy ratio show a trend on the rise. Capital adequacy ratio is still high enough, i.e. 17.4 percent. Banking liquidity, including the flow of liquidity in the money market, further improved interbank along with the reduction of segmentation and increased third-party funds. Differences in stress test results in the United State of America and in Indonesia because in banking as general in Indonesia was different with the banks in America. In America, many banks that play derivatives, so the loss is great, because it needs an injection of new capital. Meanwhile, banking in Indonesia has very minimal contact with derivatives. Yet there was the presence of the other factors that affecting stock price movements that is a factor of the value of the rupiah against the US $ because the currency is used in various international transactions as the financing of imported goods, the result of export receipts payments of foreign debt and so forth. Furthermore, the aim of this research is to figure out how big influence on banking stock price movements and exchange rates against the IHSG (composite stock price index). Based on the result of the study, the banking stocks have a positive influence on the composite index and then exchange rate has a negative influence against the composite index.